2009
DOI: 10.1111/j.1439-0426.2009.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining winter trophic habitat of juvenile Gulf Sturgeon in the Suwannee and Apalachicola rivermouth estuaries, acoustic telemetry investigations

Abstract: Summary Three automated listening post‐telemetry studies were undertaken in the Suwannee and Apalachicola estuaries to gain knowledge of habitats use by juvenile Gulf Sturgeons (Acipenser oxyrinchus desotoi) on winter feeding grounds. A simple and reliable method for external attachment of small acoustic tags to the dorsal fin base was developed using shrink‐tubing. Suspending receivers on masts below anchored buoys improved reception and facilitated downloading; a detection range of 500–2500 m was realized. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 24 publications
(49 reference statements)
3
41
1
Order By: Relevance
“…Our data on the reduced macrobenthic density assemblages indicates comparatively high mean values of 16 801 m −2 by station across the study area (see Table S1 for details by zone and season). Harris et al (2005) and Sulak et al (2009) indicated that areas with high benthic density serve as a proxy for detecting critical Gulf sturgeon feeding habitat, and our data support this assertion. However, macrobenthic density patterns were spatially variable even within a single coastal system like the Pascagoula River estuary, as ranked group macrobenthic similarity patterns and associated HMD indices indicated that west zone assemblages were more similar and less dispersed compared to east zones.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our data on the reduced macrobenthic density assemblages indicates comparatively high mean values of 16 801 m −2 by station across the study area (see Table S1 for details by zone and season). Harris et al (2005) and Sulak et al (2009) indicated that areas with high benthic density serve as a proxy for detecting critical Gulf sturgeon feeding habitat, and our data support this assertion. However, macrobenthic density patterns were spatially variable even within a single coastal system like the Pascagoula River estuary, as ranked group macrobenthic similarity patterns and associated HMD indices indicated that west zone assemblages were more similar and less dispersed compared to east zones.…”
Section: Discussionsupporting
confidence: 78%
“…New captures were tagged with T-bar and PIT tags as described by Heise et al (2004). Juvenile and subadult fish were tagged externally at the base of the dorsal fin (Sulak et al 2009, Havrylkoff et al 2012) with uniquely coded low-powered acoustic tags (either Model V9-2L or V13-1L; 69 kHz; 90 s mean random delay; VEMCO). Adult fish were tagged internally (USFWS 1993, Moser et al 2000 with high-powered uniquely coded and coated (clear Platinum Silicone Elastomer) V16-6H acoustic tags (69 kHz; 90 s mean random delay).…”
Section: Gulf Sturgeon Tagging Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on juvenile in the field have mainly concerned large juveniles (above 60 cm long or greater than 2 years of age) such as the Gulf sturgeon (Acipenser oxyrinchus desotoi) (Harris et al, 2005;Sulak et al, 2009), the green sturgeon (Acipenser medirostris) (Lindley et al, 2011) or the white sturgeon (Acipenser transmontanus) (Parsley et al, 2008). Knowledge is poorly developed in our understanding of habitat use and migration tactics in juveniles, and telemetry studies on released fish could improve our understanding of sturgeon life histories and stocking program sustainability (Gessner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%